A NEW LOOK AT THE CASTLE OF GOOD HOPE, AND ITS SYMBOLIC IMPORTANCE - Bisset, W.M. (Scientia Militaria - South African Journal of Military Studies, 2012)
The Castle of Good Hope has been described as unquestionably the 'oldest and historically the most interesting building in the country'.1 Yet it is often forgotten that its development as a showplace reminding countless visitors of South Africa's early architectural achievements and European roots, is a recent phenomenon which received its most significant boost at the Van Riebeeck Festival in 1952.